PROTOTYPE PENDETEKSI KEBOCORAN GAS LPG DENGAN INFORMASI MODUL GSM BERBASIS ARDUINO - Hafid Syaifullah (Jurnal Sistem Informasi dan Komputer (JSIKOM), 2020)
The use of LPG as a fuel alternative to fossil fuels may be more effective and practical. But considering this type of fuel has no color, and is classified as a highly flammable type, if there is a slight leak and the handler is late, that is can cause material losses as well as fatalities. This research aims to (1) create a prototype Arduino-based that can detect LPG gas leak using MQ-2 sensor, Buzzer, and GSM Module. (2) provides information to the user that there is a LPG gas leak. This research uses research and development methods. This research produces a gas leak detector technology system that (1) integrates MQ2, Arduino UNO, Buzzer and GSM Module, if the detected gas concentration level is â‰¥5000 PPM, this prototype will provide information on the presence of gas leakage to the user through four outputs, LCD for displays the results of reading the concentration of gas, buzzer as an alarm, and the GSM module for sending sms and making phone calls. (2) This warning information will allow users to reduce the risks and potential dangers caused by LPG gas leak.